Efektivitas Edukasi Kesehatan Lingkungan Rumah terhadap Peningkatan Pengetahuan Dan Efikasi Diri Ibu dalam Pengasuhan Anak Berkebutuhan Khusus di SLB Negeri Meulaboh Kabupaten Aceh Barat - Qasrina Qasrina; Ernawati Ernawati; Safrizal Safrizal; Susy Sriwahyuni; Firman Firdauz Saputra (Universitas Pahlawan Tuanku Tambusai, 2026)
A healthy home setting plays a vital role in supporting the developmental progress of children with special needs, while a mother's ability toestablish such conditions is strongly shaped by the level of knowledge and self-efficacy she possesses. This research was conducted toassess how effective home-based environmental health education is in enhancing maternal knowledge and self-efficacy among mothers who care for children with special needs at SLB Negeri Meulaboh, West Aceh Regency. Using a quasi-experimental design with a non-equivalent control group pretest-posttest format, the study involved 63 participants split into an experimental group (n=32) that receivededucational sessions delivered through home visits, and a control group (n=31) that received no such intervention. Statistical testing wascarried out using McNemar's test, the Wilcoxon Signed-Rank test, and the Mann-Whitney U test. The results revealed a statisticallysignificant rise in knowledge across both groups (p<0.001); however, the gain in self-efficacy proved more uniform within the experimental group, where every single participant demonstrated improvement, whereas the control group still included several participants whose scores declined. Comparisons made between the two groups following the intervention further confirmed that the experimental group attained markedly higher scores in both knowledge and self-efficacy relative to the control group (p<0.001). Overall, these outcomes suggest that home environmental health education serves as an effective means of boosting both maternal knowledge andself-efficacy, pointing to its viability as a family-centered promotive intervention model that other special-needs schools with comparable populations could potentially adopt.